Intergenerational Actuarial Fairness When Longevity Increases: Amending the Retirement Age - Bravo, Jorge M. (2021)
Bravo, J. M., Ayuso, M., Holzmann, R., & Palmer, E. (2021). Intergenerational Actuarial Fairness When Longevity Increases: Amending the Retirement Age. (pp. 1-41). (CESifo Working Papers; No. 9408). Munich Society for the Promotion of Economic Research ‐ CESifo GmbH. https://ssrn.com/abstract=3961911